Pemberdayaan Napi Perempuan Lapas Way Hui Melalui Kerajinan Rajutan Dan Perhitungan Penentuan Harga Jual Produk - Halimah Halimah; Sushanty Saleh; Pebrina Swissia (Politeknik Negeri Sriwijaya, 2019)
Female prisoners in these prisons become prisoners because they are entangled in various types of criminal law with various crimes committed by women such as due to many factors, leading to reasons for fulfilling the needs of those concerned. For this reason, there is a need for guidance for female prisoners as a form of self-empowerment to improve human resources in the form of life skills. Coaching skills provided by the Proposal Community Procurement team, namely training in the form of handicraft knitting. Knitted handicrafts that have been produced by inmates at the A Way Hui class II prisons include prayer hats, cellphone wallets, restleting wallets, and various kinds of brooches. Knitted products have a fairly high exclusivity value. These female prisoners are expected to succeed in making / producing creative and innovative knitted works seen from various aspects, namely aspects of material selection aspects, in addition the female prisoners are also given training to determine the cost of production and cost of goods sold from their knits.